Antigastritis effects of Armillariella tabescens (Scop.) Sing. and the identification of its anti-inflammatory metabolites. (22nd January 2018) - Lee, Seulah; Lee, Dahae; Park, Jun Yeon; Seok, Soonja; Jang, Tae Su; Park, Hyun Bong; Shim, Sang Hee; Kang, Ki Sung; Kim, Ki Hyun
Abstract: Objectives: This study demonstrates the biological and chemical analysis of the mushroom Armillariella tabescens (Scop.) Sing. (Tricholomataceae). Methods: Chemical structures of the isolates were determined by 1D and 2D NMR, and ESI-MS, as well as comparison with previously reported data. All isolates were tested for anti-inflammatory effects based on their ability to inhibit LPS-stimulated nitric oxide (NO) production in RAW264.7 cells. Key findings: We found that the MeOH extract of the fruiting bodies of A. tabescens showed antigastritis activity against ethanol-induced gastric damage in rats and notably reduced the gastric damage index compared to control in a concentration-dependent manner. Chemical investigation of the MeOH extract led to the isolation of four steroids (1 –4 ), three alkaloids (5 –7 ), two nucleic acids (8 –9 ) and four fatty acids (10 –13 ). This is the first study to report the identification of all isolates, except for compound 7, from A. tabescens . Compounds 1, 2, 3, 4 and 10 showed inhibition on LPS-stimulated NO production. Treatment with compound 10 inhibited expression of iNOS, COX-2, phospho-IKKα, IKKα, phospho-IκBα, IκBα and NF-kappa B in LPS-stimulated RAW264.7 cells. Conclusions: Compound 10 likely contributes to the health benefits of A. tabescens as an antigastritis agent through its anti-inflammatory effects.